The effect of shift workload on the sleep quality of nurses at Bekasi Regency Hospital - Tantular, Gabriella; Montolalu, Ivan Adrian; Melati, Rima; Ruhdiat, Rudi; Syafira, Eka Suci; Abrar, Ligadhea (Science Midwifery, 2025)
Nurses form a very important arm of healthcare providers that offer direct patient care services in treatment facilities. Constant shift work is typical to the nursing profession more so in hospitals that are opened round the clock medical facilities. The major challenge encountered is the lack of perfect correlation between shift workload and quality of sleep among the nurses of RSUD Bekasi. Therefore, the purpose of the study is to established the correlation between sleep quality and shift workload of the nurses in RSUD Kabupaten Bekasi. The study adopts a quantitative research approach with observational analytical research design and cross-sectional study design. The population comprises the nurses who work at night shift in the Bekasi District Hospital. The sample was purposively selected in this study. The research variables are shift workload and sleep quality. Data collection involved the use of the Occupational Fatigue Exhaustion Recovery (OFER) and the Pittsburgh Sleep Quality Index. (PSQI). Descriptive statistics were used to compare variables during data analysis by employing statistical tests. The study involved 203 respondents, with the majority being female (58.9%) and working in inpatient wards (76.7%). The results of the statistical test show a significant relationship between shift workload and sleep quality (p<0.001). The higher the shift workload, the worse the nurses' sleep quality. There is a significant correlation between shift workload and nurses' sleep quality at the Bekasi District Hospital. The research recommends a reconsideration of the shift work system to maintain the well-being of nurses and the quality of healthcare services.